Testing computer software - Kaner, Cem (Wiley computer publishing, 1999)
Includes bibliographical references (pages 437-450) and index.; This book will teach you how to test computer software under real-world conditions. The authors have all been test managers and software development managers at well-known Silicon Valley software companies. Successful consumer software companies have learned how to produce high-quality products under tight time and budget constraints. The book explains the testing side of that success.